Flow-based scheme for time-constrained data gathering in wireless sensor networks. (2016) - Almi'ani, Khaled; Viglas, Anastasios; Schalekamp, Frans; Abrishambaf, Reza
We consider the problem of data gathering in a wireless sensor network using a single mobile element. The solution must involve a combination of a mobile element visiting a subset of the nodes (caching points), while other nodes communicate their data to the caching points in a multi-hop communication paradigm. The caching point nodes are selected with the aim of reducing the number of hops, a message originated from a node must travel to reach the nearest caching point. In this paper, we propose a flow-based algorithm that iteratively constructs the mobile element tour and the multi-hop routing trees. By transforming the topology of the network into maximum flow instance, our approach aims to construct its solution to reduce the overall traffic in the network. We evaluate our algorithm by comparing its performance with best comparable well-known algorithms from the literature.